On the 'front lines' of the classroom: moral education and Muslim students in French state schools - Wesselhoeft, Kirsten (Oxford review of education, 2017)
This paper examines the role of the French state school classroom as a scene of moral pedagogy from the point of view of the French state and Muslim community activists. I argue that in both sets of discourses, the state school classroom is consistently figured as the front lines of a battleground, in which teachers, students, and parents are all combatants, but the sides and stakes of the battle are drawn differently. In each account, though, the stakes of the battle centre on the moral education of the rising generation. The state discourses fit with the history of French pedagogical theory since the inception of the state schools, and mark a recent 'return of the moral' in French public discourse and policy making. In response to the increased securitisation of the state school classroom in the aftermath of the attacks of January and November 2015, French Muslim activists have addressed a variety of conflicts related to the schools as a single coordinated fight against Islamophobia, discrimination, and persistent inequalities. By both paralleling and inverting the state's 'battleground' rhetoric in their critiques, these activists situate themselves at the heart of the national conversation about how to form the rising generation as ethical subjects.